Pengaruh Attention, Interest, Desire, Action Terhadap Efektifitas Perikalan Perbankan Bank Jatim di Jawa Timur Melalui Pengendalian Teknologi Informasi Kompetitif - Iswahyudi, Gatot; Sustiyatik, Enni; Rahayu, Budi (Jurnal Ilmiah Raflesia Akuntansi, 2023)
Bank Jatim has recently won the Indonesia Best Bank Awards 2023 for The Provision of Facilities and Market Access for MSMEs in the category of BPD (BankJatim, 2023). The award recognizes Bank Jatim's financial performance and healthy condition in 2023. The bank's development of online services through the dynamic and competitive brand Jconnect has allowed for more efficient banking operations and increased market penetration. In addition to its commitment to economic growth in the East Java region, Bank Jatim is also dedicated to developing technology and information services for a more personalized and responsive banking experience.This study aims to analyze the effect of Attention, Interest, Desire, and Action (AIDA) and Information Technology Readiness (ITR) on the effectiveness of banking advertisement at Bank Jatim in East Java through competitive technology control. A total of 230 Bank Jatim customers in East Java were randomly selected as respondents for the primary data collected through a questionnaire. Structural Equation Modeling (SEM) was used to analyze the data and test the hypothesized relationships. The findings indicate that ATT, DSR, and EPP have a significant effect on the effectiveness of banking advertisement, whereas ITR and ACT have a significant effect on the effectiveness of banking advertisement through competitive technology control. The results also suggest that Bank Jatim should focus on developing its online services, increasing interaction with customers, and implementing effective advertising strategies to enhance the effectiveness of banking advertisement. In conclusion, the implementation of information technology in banking is crucial for enhancing the quality of services and advertising effectiveness. Bank Jatim should consider the factors that affect online service usage and implement appropriate strategies to improve effectiveness. The findings of this study have implications for other banking institutions seeking to improve their service quality and advertising effectiveness, as well as for researchers and students interested in exploring the interplay of technology and advertising in the banking industry.